The Effect of Practical Exercises for the Technique of Ballistic Training to Develop Some Functional Capabilities of the Goalkeepers of the National Youth Football Team) - Ehab Mohammed Farhan; Abdulwahhab Ghazi Hammoodi (Institute of Medico-legal Publications Pvt Ltd, 2022)
The importance of the research lies by recognizing the importance of using the Ballistic training method,which is one of the important methods in explosive strength training and the characteristic force withspeed, and this method works by overcoming other traditional strength training such as weight lifting,and overcoming the shortage in speed as a result of these exercises in a position, a set of specialexercises for this method to train goalkeepers for the youth national football team, and the researcherdecided to tackle the problem according to the following question:The question? ... Do special exercises prepared by the researcher using the method of Ballistic trainingcontribute to raising the level of development of some functional abilities of the individuals of a researchspecimen...?The answer to this question is through the results that the researcher will obtain for all field proceduresthat he will prepare and implement on the research specimen, and the research aims to develop a setof applied exercises for the method of Ballistic training to develop some functional abilities of theindividuals of the research sample, as well as to identify the rate of development Also, as for theimposition of the research, there were statistically significant differences between the results of the preand post tests for the values of some functional abilities and in favor of the results of the post tests of theindividuals of the research sample, and the researcher used the experimental method in a comparativemethod for one group, and the research specimen consisted of four Goalkeepers for the Iraqi nationalyouth football team, and then the sample was tested with pre-tests of functional capabilities, after whichthe special applied exercises according to the Ballistic method were applied to the members of theresearch specimen, as the duration of their application lasted eight weeks with three training units perweek, after which Post-tests were conducted on them, and the statistical application Statistical Packagefor the Social Science (SPSS) was used to obtain and discuss the results of tests of the goalkeepers.The special applied exercises according to the Ballistic method have a positive effect on the functionalcapabilities of the goalkeepers. The recommendations, the use of the Ballistic training method in thegoalkeeper’s position was emphasized because of its clear importance in the development and upgradingof the career capabilities of the goalkeepers in football.